Orgao - Uma publicaçao "No Existen Los Limites" : (Qual o prazer possivel ?). (São Paulo : FAAP - fundação Armando Alvares Penteado, 1998)
Hovdenakk, Per ; Ono, Yoko ; Mammi, Lorenzo ; Heske, Marianne ; Tavares, Ana ; Lemos, Tonico ; Verzuti, Erika ; Cunha, Alexandre da ; Furlong, Patricia ; Marchetti, Claudia ; Mariotti, Gilberto ; Schoenacker, Monica ; Cretti, Claudio ; Pessoa, Solange ; Spaniol, José ; Viriato, Edilson ; De Mello, Vicente ; Leirner, Jac ; Cipis, Marcelo ; Almeida, Efraim ; Lacerda, martha ; Kaepler, Sabine ; Malta, Antônio ; Restife, mauro ; Marepe ; Loeb, Lucia Mindlin
Orgao - Uma publicaçao "No Existen Los Limites", São Paulo, stembro 1998
boek